Drawing QSers' mind : a cognitively-informed critical metaphor analysis tracing the cultural model of the Quantified Self - Cong, Mu (2021)
With the spread of digital surveillance technologies from the domains of military and medical to those of personal and everyday, we have seen invention of novel metaphors to conceptualise our daily practices as well as our selves in relation to such emerging technologies as Big Data, which aggregate, crunch and sort our personal information collected from the sensors and cameras embedded ubiquitously now in our living environment, known as an ‘infosphere.’ They sort our selves in a new way, thus altering our self-concept and informing a new, data-driven self culture. The epitome of this trend is the Quantified Self (QS) movement. The participants, known as QSers and who are prosumers, seek ‘self knowledge through numbers’ generated by commercial self-monitoring devices, such as Fitbit and Mi Band. They put their bodily activities under self-surveillance for becoming the experts of self-management and self-optimisation. The global popularisation of QS culture has three implications for our human condition. First, it creates a sham utopia. The platform economy brings into being a precariat, who struggle daily for security and success. In response, the QS gadget companies advertise to a white, middle-class clientele that they can offer them both. Second, it promotes neoliberal reflexive practices and discourse of selfhood. QS culture is historically rooted in the American success culture, which prizes individual success made through self-reliance and continuous self-reinvention. This culture foregrounds personal agency in influencing individuals’ living conditions and life chances, while discounting social structural factors. Third, it makes privacy, hence self-reinvention, problematic. When it comes to the issue of ownership of QSers’ self-data, it is ambiguous to whom they belong and whether the QSers can still enjoy ‘the right to forget’ once the data are uploaded to the cloud. Sociologists have studied the QS culture and its relations to neoliberalism, but they have not tackled the QSers’ subjective experience, particularly their own discourse and mind, in a systematic manner. Meanwhile, although cognitive linguists have had the tools to probe QSers’ discourse, mind and culture, or the cognitive schemas and structures that influence QSers’ beliefs and behaviours, they have not done so, either. Therefore, my thesis contributes to the QS research by cross-fertilising, or transgressing the boundaries of, the disciplines, adding to it another dimension of cognitively-informed critical metaphor analysis of QSers’ mind. I have applied critical discourse analysis for both literature review and empirical analysis. For the empirical chapters, I have systematically mapped out the relations between a QSer’s use of conceptual metaphors in a blog post and the underlying cognitive schemas, which constitute a cultural model of Quantified Self for a sample consisting of a small corpus (52,177 words in total). I used the methods of MIP and SMA to identify the linguistic, conceptual and systematic metaphors in a prototypical blog post, sampled from my proprietary corpus of 40 unique QSers’ blog texts. Based on the identifications, I further traced three metaphor trajectories, or the blogger’s thought patterns, that involved the self, QS tools and data. I found that 1) the blogger thought his HEALTH CONDITIONS WERE OBJECTS that could be managed and controlled with hard work and help from self-monitoring devices, thus giving him a sense of self-made success and being in control. 2) He thought the QS TOOLS WERE PEOPLE, who were productive, capable, intelligent and friendly. This reflects the infosphere’s structural influence on people’s cognition, which decentres the humans and places them on par with other informational agents. 3) He conceived that his DATA WERE VALUABLE RESOURCES, whose ownership was unclear. Meanwhile, alternative metaphors that were relegated to the background by the QS culture were revived and discussed along these trajectories. Altogether, they have demonstrated the framing effects of QS metaphors, i.e. the metaphors can both enable and constrain a QSer’s conceptualisation of self in connection with data and self-control.